Răspuns :
Aplici formula sin (x-y)=sinxcosy-cosxsiny
sin ( x - pi/4) = sin(x)cos(pi/4) - cos(x)sin(pi/4)=
sin(x)cos45° - cos(x)sin45°
cos45°=sin45°=√2/2
Rezulta ca:
sin(x)cos45° - cos(x)sin45° = sinx√2/2 - cosx√2/2= √2/2( sinx- cosx)
sin ( x - pi/4) = sin(x)cos(pi/4) - cos(x)sin(pi/4)=
sin(x)cos45° - cos(x)sin45°
cos45°=sin45°=√2/2
Rezulta ca:
sin(x)cos45° - cos(x)sin45° = sinx√2/2 - cosx√2/2= √2/2( sinx- cosx)
π/4 = 180°/4 =45°
sin(x - 45°) = sinxcos45° - sin45°cosx = sinx · √2/2 - √2/2 · cosx =
= √2/2(sinx - cosx) /
sin(x - 45°) = sinxcos45° - sin45°cosx = sinx · √2/2 - √2/2 · cosx =
= √2/2(sinx - cosx) /